Antioxidant Activity Assay of Combination of Purified Extract of Banana Peel (Musa Paradisiaca Sapientum) and Andrographis Paniculata Leaves - Jastria Pusmarani M.Sc., Apt. (Journal of Global Pharma Technology, 2020)
Antioxidant is a compound that able to postpone, slowdown and prevent free radical reaction which able to postpone degenerative disease. Banana peel (Musa Paradisiaca Sapientum) and Andrographis paniculata contain flavonoid compound which have antioxidant activity. The aim of this study is to measure antioxidant activity of the combination of banana peel extract and Andrographis paniculata to DPPH free radical (2,2-difenil-1-pikrilhidrazil). Extraction process of banana peel using methanol, meanwhile Andrographis paniculata using ethanol 70%. Extract purification conducted using n-hexan and ethyl acetate. This study using combination of the purified extract of banana peel and Andrographis paniculata with the following comparison consecutively (1:10) (1:1) (2:1) (1:2) (0:1) concentration of  20,40, 60, 80 and 100 ppm, measured their antioxidant activity with DPPH method using visible spectrophotometry, thus resulted in IC50value. IC50value for the combination of purified extract of banana peel and Andrographis paniculata (0:1) as many as 256.76 ppm, the combination of purified extract of banana peel and Andrographis paniculata (1:1) as many as 140.33 ppm, the combination of purified extract of banana peel and Andrographis paniculata leaves (1:2) as many as 110.05 ppm, the combination of purified extract of banana peel and Andrographis paniculata (2:1) as many as ppm, the combination of purified extract of banana peel and Andrographis paniculata (1:0) as many as 184.13 ppm. The result can be concluded that combination of purified extract of banana peel and Andrographis paniculata have an antioxidant activity even though in moderate category included purified extract of combination of of banana peel and Andrographis paniculata with comparison (0:1) (1:2), (2:1), (1:1) and (1:0) have medium antioxidant activity.